European and Ukrainian Requirements for the Registration of Biofungicides: Regulatory Differences and Pathways to Harmonization - Hrynzovskyi, Oleksandr; Hrynzovska, Anastasiia; Vavrinevych, Olena; Koval, Ruslan (The Ukrainian Scientific Medical Youth Journal, 2025)
biofungicides based on microorganisms and their metabolites are increasingly considered as alternatives to chemical fungicides in agriculture and medicine within the framework of the One Health concept. In 2022, the European Union adopted a comprehensive set of updates to Regulation (EC) No 1107/2009 (Regulations (EU) 2022/1438–1441), which established specific approval criteria for microorganisms, new data requirements, and uniform principles of evaluation. At the same time, Ukraine continues to rely on the Law “On Pesticides and Agrochemicals” and Governmental Resolution No. 295 (1996), which lack specific provisions for microbial plant protection products, creating barriers to the registration and use of modern biofungicides. In this article, we compare the EU and Ukrainian requirements for the registration of biofungicides, identify key regulatory gaps (strain identification/WGS, antimicrobial resistance assessment, metabolites, manufacturing quality, “low-risk” principles, transitional provisions), and propose a stepwise roadmap for harmonization aligned with the One Health approach. Harmonizing Ukrainian requirements with EU regulations will enable transparent registration of biofungicides, enhance human and environmental safety, accelerate the market entry of low-risk bioproducts, and strengthen Ukraine’s integration into the European regulatory framework.